Mulheres, memória e violência: representações e experiências no âmbito do conflito armado colombiano - Velasco, Martha Cecilia Machado (2022)
The Colombian Armed Conflict is with no doubt a situation in which the role of the victim took relevance in the last years, the process of that memory reconstruction in which the individuals that are connected direct and indirectly to this phenomenon have converted into an essential tool to narrate what happened and at the same time, it’s an essential element in which the Colombian folk dialogue about peace on their territories. This research focuses its interest in the voice of the female victims of the conflict and its histories through the process of reconstruction of the memory as the peace bearers in their communities. For this research, it’s carried out by a bibliographic and documental labor that addresses the different theoretical concepts starting from the human studies; in the same way it complements the research with the use of ethnography and the semi-structured interview as the main tool to collect data in the countryside. In this context, it seeks to understand women’s role and political performance in the collective construction of the social and historical memories based on their experiences in the armed conflict scenario on the regions of Cauca and the Amazonas. At the same time, it looks to analyze and understand the memories of women’s daily life in the armed conflict context, as well as understanding the power relations that are established on the women’s role in the armed conflict territories and distinguish the representations that women produce of themselves and their lifestyles in violence contexts.